Emission of poly and perfluoroalkyl substances, UV-filters and siloxanes to air from wastewater treatment plants. (November 2016) - Shoeib, Mahiba; Schuster, Jasmin; Rauert, Cassandra; Su, Ky; Smyth, Shirley-Anne; Harner, Tom
Abstract: The potential of wastewater treatment plants (WWTPs) to act as sources of poly and perfluoroalkyl substances (PFASs), volatile methyl siloxanes (VMSs) and organic UV-filters to the atmosphere was investigated. Target compounds included: PFASs (fluorotelomer alcohols (FTOHs), perfluorooctane sulfonamides/sulfonamidoethanols (FOSAs/FOSEs), perfluroalkyl sulfonic acids (PFSAs) and perfluroalkyl carboxylic acids (PFCAs)), cyclic VMSs (D3 to D6), linear VMSs (L3 to L5) and eight UV-filters. Emissions to air were assessed at eight WWTPs using paired sorbent-impregnated polyurethane foam passive air samplers, deployed during summer 2013 and winter 2014. Samplers were deployed on-site above the active tank and off-site as a reference. Several types of WWTPs were investigated: secondary activated sludge in urban areas (UR-AS), secondary extended aeration in towns (TW-EA) and facultative lagoons in rural areas (RU-LG). The concentrations of target compounds in air were ∼1.7–35 times higher on-site compared to the corresponding off-site location. Highest concentrations in air were observed at UR-AS sites while the lowest were at RU-LG. Higher air concentrations (∼2–9 times) were observed on-site during summer compared to winter, possibly reflecting enhanced volatilization due to higher wastewater temperatures or differences in influent wastewater concentrations. A significant positive correlation was obtained between concentrations in air and WWTP characteristics (influent flow rate and population in the catchment of the WWTP); whereas a weak negative correlation was obtained with hydraulic retention time. Emissions to air were estimated using a simplified dispersion model. Highest emissions to air were seen at the UR-AS locations. Emissions to air (g/year/tank) were highest for VMSs (5000–112, 000) followed by UV-filters (16–2000) then ΣPFASs (10–110). Graphical abstract: Highlights: Highest emissions to air from WWTPs were for the VMS, followed by UV-filters and PFASs. Highest emissions to air were for activated sludge WWTPs that are typical in urban areas. Emissions to air were well correlated to WWTP operating parameters. Organic UV-filter compounds are reported in ambient air for the first time. Abstract : Thousands of kilograms of organic pollutants (poly-perfluoroalkyl substances, volatile methyl siloxanes and UV-filters) are released to air each year from wastewater treatment plants.